Urbanization and internal migration in 45 Philippine cities during the 1960's - Mariano, Vicente D. 1947- (Quezon City Population Institute, University of the Philippines, 1975)
Abstract

The study covers the urbanization and internal migration experiences of
forty-five Philippine cities in the 1960 – 1970 intercensal period. The hypothesis of the study is that there is an urbanization-internal migration pattern in these cities with the level of urbanization determining the level of internal migration. The relationship is proposed to be a workable basis in classifying Philippine cities and in identifying centers of functionally integrated areas in the country. Twenty-six variables were used in principal component analysis to determine the presence of and
urbanization factor (or component) in the cities under study. After it has been established that such a factor was present, urbanization scores (indicating the level of urbanization) were computed and correlated with percent net population gain or loss. The results obtained suggest that in classifying Philippine cities and in determining the administrative centers (including regions) in the country the urbanization-internal migration framework is feasible.
Thesis (M.A. in Demography)--University of the Philippines Diliman.
Keywords: Cities and towns -- Philippines; Migration, internal -- Philippines; Urbanization -- Philippines